SGK1, a Critical Regulator of Immune Modulation and Fibrosis and a Potential Therapeutic Target in Chronic Graft-Versus-Host Disease - Lu, Run-qing; Zhang, Yin-yin; Zhao, Hai-qiu; Guo, Rong-qun; Jiang, Zhong-xing; Guo, Rong (Frontiers in Immunology, 2022)
Patients with severe chronic graft-versus-host disease (cGVHD) always experience debilitating tissue injury and have poorer quality of life and shorter survival time. The early stage of cGVHD is characterized by inflammation, which eventually leads to extensive tissue fibrosis in various organs, such as skin and lung, eventually inducing scleroderma-like changes and bronchiolitis obliterans syndrome. Here we review the functions of serum- and glucocorticoid-inducible kinase 1 (SGK1), a hub molecule in multiple signal transduction pathways and cell phosphorylation cascades, which has important roles in cell proliferation and ion channel regulation, and its relevance in cGVHD. SGK1 phosphorylates the ubiquitin ligase, NEDD4, and induces Th cells to differentiate into Th17 and Th2 phenotypes, hinders Treg development, and promotes inflammatory fibrosis. Phosphorylation of NEDD4 by SGK1 also leads to up-regulation of the transcription factor SMAD2/3, thereby amplifying the fibrosis-promoting effect of TGF-β. SGK1 also up-regulates the inflammatory transcription factor, nuclear factor-κB (NF-κB), which in turn stimulates the expression of multiple inflammatory mediators, including connective tissue growth factor. Overexpression of SGK1 has been observed in various fibrotic diseases, including pulmonary fibrosis, diabetic renal fibrosis, liver cirrhosis, hypertensive cardiac fibrosis, peritoneal fibrosis, and Crohn’s disease. In addition, SGK1 inhibitors can attenuate, or even reverse, the effect of fibrosis, and may be used to treat inflammatory conditions and/or fibrotic diseases, such as cGVHD, in the future.